Visual similarity-based fashion recommendation system - Ay, Betul; Aydin, Galip (Elsevier, 2021)
Fashion recommendation systems are designed to retrieve a ranked list of catalog images similar to the target catalog image. These systems are crucial in helping customers move toward potential buying decisions from recommended products. Catching true correlation between similar product recommendations and user satisfaction will exponentially improve sale experience of companies. One of the major tasks in fashion recommendation systems is accurately finding similar images for a given product image. © 2021 Elsevier Inc. All rights reserved.
Keywords: Convolutional neural network (CNN); Fashion recommendation system; Generative adversarial network (GAN); Image similarity; Visual search and similarity